Histori Filantropi: Tinjauan Teori Postmodern - Puji Purwatiningsih, Aris; Hermawan Adinugraha, Hendri (ZISWAF, 2018)
Postmodern is a breeding effort, epistemological innovation, so anthropology becomes more adaptive and productive. This can be demonstrated through the application of his theory in practice and philanthropy models. This paper aims to describe the history of philanthropy in terms of the perspective of postmodern theory. The results of the literature review indicate that at first the emergence of the philanthropy movement was the way of the rulers of the time to maintain the stability of public security by providing assistance to the community, but in the postmodern period turned into non-profit social institutions or institutions that serve as mediators of donors to the needy. Philanthropy, initially only in the form of goods aimed at relieving and meeting the needs of a deficient society, in the postmodern era can develop into donor body parts, smiles and even empathy can be referred to as philanthropy. Alms that were originally human goods, the postmodern expanded that spread the science, moving the masses can also be called philanthropy.